Conflicts of interest in dermatology - Williams, Hywel C.; Naldi, Luigi; Paul, Carle; Vahlquist, Anders; Schroter, Sara; Jobling, Ray (Scandinavian University Press, 2006)
Conflicts of interest exist in dermatology when professional judgement concerning a primary interest, such as research validity, may be influenced by a secondary interest, such as financial gain from a for-profit organization. Conflict of interest is a condition and not a behaviour, although there is clear evidence that gifts influence behaviour. Little has been written about conflicts of interest in dermatology. This series of papers raises awareness of the subject by exploring it in greater depth from the perspective of a dermatology researcher, an industry researcher, a dermatology journal editor, a health services researcher and a patient representative. Collectively, they illustrate the many ways in which conflicts can pervade the world of dermatology publications and patient support group activities.